Mitochondrial integrity: preservation through Akt/Pim-1 kinase signaling in the cardiomyocyte - Sussman, Mark A (2009)
The central role of mitochondria as mediators of cell survival is indisputable and gathering increasing attention as a focal point for interventional strategies to mitigate apoptotic cell death in the wake of cardiomyopathic injury. A legacy of signal transduction studies has proven that mitochondrial integrity can be enhanced by kinases involved in cell survival. Among the many survival signaling cascades under investigation, the wide-ranging impact of Akt upon mitochondrial biology is well known. However, despite years of investigation, emerging research continues to reveal new mechanisms governing the protective effects of Akt signaling in the context of cardiomyocyte mitochondria. This review focuses on two emerging pathways that mediate preservation of mitochondrial function downstream of Akt: hexokinase and Pim-1 kinase.